Fine cooking roasting : favorite recipes & essential tips for chicken, beef, veggies & more / Editors and contributors of Fine Cooking - Fine Cooking
From the most trusted name in food, this book serves up the best recipes and techniques so home cooks can successfully produce bold-flavoured, juicy meat and vegetable dishes time and again. It includes page after page of informative tips with over 150 mouthwatering colour photographs.